The Principle of Adult Education (AE) through the Community Empowerment in Household Waste Management at Bening Saguling Foundation - Indra Indra (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2018)
Adult Education (AE) is the education which is more oriented to realistic application towards what is felt and faced in daily life. Waste problems in modern life have been very crucial concern and issues to be solved. Through the empowerment which puts forward the change of the mindset about waste from a problem into a blessing, establishment of waste management institution, strengthening management capacity through training and mentoring continuously can be one of the solutions in household waste management. The community empowerment in household waste management can increase family’s income and conserve the environment, so that the community which is independent economically and sustainable environment can occur.